Odontoid fracture with accompanying severe atlantoaxial instability in elderly patients: analysis of treatment, adverse events, and outcome - Kreinest, Michael; Raisch, Philipp; Hörnig, Lukas; Vetter, Sven Y.; Grützner, Paul Alfred; Jung, Matthias (Journal of Clinical Medicine, 2024)
(1) Background: In elderly patients with type II odontoid fractures, accompanying severe atlantoaxial instability (AAI) is discussed as a marker possibly warranting more aggressive surgical therapy. This study aimed to characterize adverse events as well as the radiological and functional outcomes of surgical vs. conservative therapy in patients with odontoid fracture and AAI. (2) Methods: Patients aged 65 years and older with type II odontoid fracture and AAI treated were included. AAI was assumed if the mean subluxation across both atlantoaxial facet joints in the sagittal plane was greater than 50%. Data on demographics, comorbidities, treatment, adverse events, radiological, and functional outcomes were analyzed. (3) Results: Thirty-nine patients were included. Hospitalization time was significantly shorter in conservatively treated patients compared to patients with ventral or dorsal surgery. Adverse events occurred in 11 patients (28.2%), affecting 10 surgically treated patients (35.7%), and 1 conservatively treated patient (9.1%). Moreover, 25 patients were followed-up (64.1%). One secondary dislocation occurred in the conservative group (11.1%) and three in the surgical group (18.8%). (4) Conclusions: Despite the potential for instability in this injury, conservative treatment does not seem to lead to unfavorable short-term results, less adverse events, and a shorter hospital stay and should thus be considered and discussed with patients as a treatment option, even in the presence of severe AAI.